Digital readiness and its effects on higher education students' socio-emotional perceptions in the context of the COVID-19 pandemic. Issue 2 (9th November 2020) - Händel, Marion; Stephan, Melanie; Gläser-Zikuda, Michaela; Kopp, Bärbel; Bedenlier, Svenja; Ziegler, Albert
Abstract: The current study investigated how ready higher education students were for emergency remote teaching due to the COVID-19 pandemic and how this influenced their socio-emotional perceptions. Results of N  = 1, 826 higher education students indicate that they seem to be ready for digital learning. A k -means cluster analysis revealed two groups of students that significantly differed with respect to their readiness for digital learning (in terms of technology equipment availability, prior experiences with e-learning, and skills for digital learning). Finally, students' socio-emotional perceptions, that is, stress-related emotions (worries, tension, joy, and overload) as well as social and emotional loneliness significantly differed due to cluster membership. Hence, the study points a need for support of higher education students in successfully coping with the challenges of emergency remote studying.